Internalisasi Nilai-Nilai Islam Melalui Budaya Sekolah Dalam Membentuk Karakter Siswa di SMA 1 Negeri Asembagus Kabupaten Situbondo - MS, Ningsih MS Ningsih (IJIT: Indonesian Journal of Islamic Teaching, 2025)
The development of the global era known as globalization, brings positive and negative impacts to human life. Controversial phenomena such as easy accessibility of information and entertainment with the rampant exposure to pornographic content, SARA content and so on that come simultaneously without control. In an effort to fortify oneself from the negative impacts of this globalization era, education is needed that provides reinforcement of Islamic values so that the attitudes (affects) and characters of Indonesian students are formed that are steady and strong in the future. This research is a qualitative research with the type of Case Study at SMAN 1 Asembagus Situbondo Regency. The results of this study are, the transformation of Islamic values into school culture in shaping student character is that teachers / schools provide information,knowledge by giving advice, reprimands and suggestions to students. Students listen / listen. Transactions of Islamic values and school culture in shaping student character are teachers / schools provide knowledge by means of habituation and continuous role models / examples to students, Teachers provide motivation in the form of awards and / gifts. Students respond / respond happily. The internalization of Islamic values through school culture in shaping student character involves teachers and schools becoming role models and role models for students. Students value their teachers' attitudes and personalities, thus voluntarily, sincerely, and consistently following their teachers' behavior (ta'dhim). Keyword: Nilai Islam, Karakter siswa, Budaya sekolah